Classification of bank account agreements - N.V. Syropiatova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper is aimed at classification of bank account agreements. There has recently been a tendency to increase in the number of their types. The Concept of the Development of Civil Legislation of the Russian Federation (2009) stated that the requirements of civil turnover in various financial services mean both expansion of the range of possible bank accounts and development of the regulation of bank account types that are already provided by legislation. Based on the obtained results, it has been suggested that significant changes should be made to Chapter 45 “Bank Account” of the Civil Code of the Russian Federation. Currently, new types of bank accounts can be distinguished. However, there is no classification in the Civil Code of the Russian Federation, which raises problems both of their theoretical and practical nature. It is also difficult to determine the location of individual types in the general system of bank account agreements. The paper considers the classifications of bank account agreements based on different grounds. Analyzing the current legislation on bank account agreements, the conclusion has been made that it is possible to classify them depending on the functions implemented. It has been suggested to differentiate between three groups of contracts: the first group includes the contracts that have common functions for all bank account agreements; the second one covers the contracts that have some specific functions that distinguish certain types of bank account agreements from each other; and the last one comprises the bank account agreements that have strictly specific functions that include contracts for special bank accounts. In accordance with this classification, the systematization of bank account agreements by determining the position of each agreement in the suggested classification has been performed.